2011
DOI: 10.1103/physrevb.83.161402
|View full text |Cite
|
Sign up to set email alerts
|

Electron-phonon interactions in bilayer graphene

Abstract: Density functional perturbation theory is used to analyze electron-phonon interaction in bilayer graphene. The results show that phonon scattering in bilayer graphene bears more resemblance with bulk graphite than monolayer graphene. In particular, electron-phonon scattering in the lowest conduction band is dominated by six lowest (acoustic and acoustic-like) phonon branches with only minor contributions from optical modes. The total scattering rate at low/moderate electron energies can be described by a simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 21 publications
11
39
0
Order By: Relevance
“…64,[83][84][85] It is noted that the intravalley electron-phonon scattering has been reported in the previous literature as mentioned in the introduction.…”
Section: Model and Ksbesmentioning
confidence: 88%
See 1 more Smart Citation
“…64,[83][84][85] It is noted that the intravalley electron-phonon scattering has been reported in the previous literature as mentioned in the introduction.…”
Section: Model and Ksbesmentioning
confidence: 88%
“…[63][64][65] Specifically, the intravalley electron-acoustic (AC) phonon coupling has been calculated by Viljas and Heikkilä 63 with the continuum theory and also by Borysenko et al 64 from first principles. To explore the intravalley electron-optical (OP) phonon coupling, the tight-binding model, density functional theory and first principles approach are employed by Viljas and Heikkilä, 63 Cappelluti et al 65 and Borysenko et al, 64 respectively. However, the intervalley electron-phonon coupling, which has been shown to play an important role in spin relaxation in rippled singlelayer graphene, 50 has not been reported in the previous literature.…”
Section: -65mentioning
confidence: 99%
“…11,15 A comparative analysis reveals several qualitative differences in the intrinsic scattering of MLG and BLG. For one, MLG has six phonon branches with two carbon atoms in a unit cell, whereas these numbers double in BLG.…”
Section: Relevant Scattering Mechanismsmentioning
confidence: 99%
“…10 A recent work based on the first-principles calculations has suggested that this discrepancy may start with the intrinsic transport properties, which results from substantial differences in electron-phonon coupling in these two materials. 11 Additionally, it is widely accepted that extrinsic factors such as charged impurities, disorder, and surface polar phonons (SPPs) can significantly alter carrier transport in graphene on a substrate, which is the most commonly used configuration. [12][13][14] Despite extensive research efforts, a comprehensive understanding of electrontransport properties in BLG is still a work in progress.…”
Section: Introductionmentioning
confidence: 99%
“…For the parameters Ω ν describing the interaction between the layers we use values in agreement with Ref. 63. It should be noted however, that in the literature a range of values (±30%) can be found for this constant 49,64,65 .…”
Section: Computational Detailsmentioning
confidence: 93%